Erythrocytes as model cells for biocompatibility assessment, cytotoxicity screening of xenobiotics and drug delivery. (1st December 2020) - Podsiedlik, Maria; Markowicz-Piasecka, Magdalena; Sikora, Joanna
Abstract: Erythrocytes (RBCs) represent the main cell component in circulation and recently have become a topic of intensive scientific interest. The relevance of erythrocytes as a model for cytotoxicity screening of xenobiotics is under the spotlight of this review. Erythrocytes constitute a fundamental cellular model to study potential interactions with blood components of manifold novel polymer or biomaterials. Morphological changes, subsequent disruption of RBC membrane integrity, and hemolysis could be used to determine the cytotoxicity of various compounds. Erythrocytes undergo a programmed death (eryptosis) which could serve as a good model for evaluating certain mechanisms which correspond to apoptosis taking place in nucleated cells. Importantly, erythrocytes can be successfully used as a valuable cellular model in examination of oxidative stress generated by certain diseases or multiple xenobiotics since red cells are subjected to permanent oxidative stress. Additionally, the antioxidant capacity of erythrocytes, and the activity of anti-oxidative enzymes could reflect reactive oxygen species (ROS) generating properties of various substances and allow to determine their effects on tissues. The last part of this review presents the latest findings on the possible application of RBCs as drug delivery systems (DDS). In conclusion, all these findings make erythrocytes highly valuable cells for in vitro biocompatibility assessment, cytotoxicity screening of a wide variety of substances as well as drug delivery. Highlights: Erythrocytes are a valuable in vitro model for cytotoxicity screening of xenobiotics. Erythrocytes can be used as a cellular model in examination of oxidative stress. Red blood cells can be successfully applied as drug delivery systems. Xenobiotics can interact with erythrocytes membrane and induce eryptosis.